Identification of a classic nuclear localization signal at the N terminus that regulates the subcellular localization of Rbfox2 isoforms during differentiation of NMuMG and P19 cells. Issue 24 (1st December 2016) - Wenzel, Manuel; Schüle, Martin; Casanovas, Sonia; Strand, Dennis; Strand, Susanne; Winter, Jennifer
Abstract : Nuclear localization of the alternative splicing factor Rbfox2 is achieved by a C‐terminal nuclear localization signal (NLS) which can be excluded from some Rbfox2 isoforms by alternative splicing. While this predicts nuclear and cytoplasmic localization, Rbfox2 is exclusively nuclear in some cell types. Here, we identify a second NLS in the N terminus of Rbfox2 isoform 1A that is not included in Rbfox2 isoform 1F. Rbfox2 1A isoforms lacking the C‐terminal NLS are nuclear, whereas equivalent 1F isoforms are cytoplasmic. A shift in Rbfox2 expression toward cytoplasmic 1F isoforms occurs during epithelial to mesenchymal transition (EMT) and could be important in regulating the activity and function of Rbfox2. Abstract :